A LINGUOCULTURAL STUDY OF GASTRONOMIC PHRASEOLOGICAL UNITS: LINGUOCULTURAL STUDY OF GASTRONOMIC PHRASEOLOGICAL UNITS - Uralova, Nigora (Журнал иностранных языков и лингвистики, 2022)
The article investigates the linguacultural examination of gastronomic phraseological units. Linguocultural examination of gastronomic phraseological units is considered within the aggregate phraseological that means and the which means of the variable fashions of phraseological gadgets. the writer emphasized nods, the slow nature of the sign of nationally-unique statistics, encoded in the means of phraseological units. the author means that considering the hassle of interaction between language and way of life, it's miles common the postulate that phraseology is the layer of the language device, which maximum virtually reflects the worldview, behavior, perception of the encompassing truth, and interpersonal relationships of people. every country has its cultural vision of the arena, is due to the way of life, behavior, traditions, nature, worldview, and tendencies of the national man or woman.